2018
DOI: 10.5897/ijeaps2018.0553
|View full text |Cite
|
Sign up to set email alerts
|

An examination of teacher candidates attitudes towards teaching profession

Abstract: Teaching profession is one of the hardest jobs of today. Teachers who raise the safeguards of our future, that is, our students should be aware of the principles, methods and techniques needed for teaching; should have taken the pedagogical formation training, should have enhanced communication skills and should closely follow science and technology with a mind open to modernization. Teachers also must carry the feeling of responsibility, have high sense of awareness and consciousness, be developed in their ow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
0
0
1
Order By: Relevance
“…It was surprising that students from the Department of Education ranked sixth even though it is a professional degree which students specially join for the teaching profession. Result of the current study are supported by Muhammet and Sarigöz (2018) which found that the attitude of students from the Department of Education was below expectation. Attitude towards any profession significantly affects the success of the person in any profession.…”
Section: Discussionsupporting
confidence: 72%
“…It was surprising that students from the Department of Education ranked sixth even though it is a professional degree which students specially join for the teaching profession. Result of the current study are supported by Muhammet and Sarigöz (2018) which found that the attitude of students from the Department of Education was below expectation. Attitude towards any profession significantly affects the success of the person in any profession.…”
Section: Discussionsupporting
confidence: 72%
“…Kartal, vd., (2012) öğretmen adaylarının öğretmenlik mesleğine yönelik tutumları ile cinsiyet, genel akademik ortalama, ailenin aylık geliri ve üniversite öncesi nerede yaşadıkları ile ilgili puanları arasında istatistiksel olarak anlamlı bir fark olmadığını saptamıştır. Ancak birtakım araştırmalar (Atalmış ve Köse, 2018;Baş ve Sarigöz, 2018;Fadlelmula, 2013;Yıldırım, 2012) kadınların öğretmenlik mesleğine yönelik daha olumlu bir tutuma sahip olduklarını sonucuna ulaşmışlardır.…”
Section: Sonuç Ve Tartışmaunclassified